Functional and Pathological Roles of AHCY - Vizán, Pedro; Di Croce, Luciano; Aranda, Sergi (Frontiers in Cell and Developmental Biology, 2021)
Adenosylhomocysteinase (AHCY) is a unique enzyme and one of the most conserved proteins in living organisms. AHCY catalyzes the reversible break of S-adenosylhomocysteine (SAH), the by-product and a potent inhibitor of methyltransferases activity. In mammals, AHCY is the only enzyme capable of performing this reaction. Controlled subcellular localization of AHCY is believed to facilitate local transmethylation reactions, by removing excess of SAH. Accordingly, AHCY is recruited to chromatin during replication and active transcription, correlating with increasing demands for DNA, RNA and histone methylation. AHCY deletion is embryonic lethal in many organisms (from plants to mammals). In humans, AHCY deficiency is associated with an incurable rare recessive disorder in methionine metabolism. In this review, we focus on the AHCY protein from an evolutionary, biochemical, and functional point of view, and we discuss the most recent, relevant, and controversial contributions to the study of this enzyme.